2009
DOI: 10.1039/b801586d
|View full text |Cite
|
Sign up to set email alerts
|

Size and composition distribution dynamics of alloy nanoparticle electrocatalysts probed by anomalous small angle X-ray scattering (ASAXS)

Abstract: Anomalous small angle X-ray scattering (ASAXS) is shown to be an ideal technique to investigate the particle size and particle composition dynamics of carbon-supported alloy nanoparticle electrocatalysts at the atomic scale. In this technique, SAXS data are obtained at different X-ray energies close to a metal absorption edge, where the metal scattering strength changes, providing element specificity. ASAXS is used to, first, establish relationships between annealing temperature and the resulting particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 49 publications
5
87
1
Order By: Relevance
“…A possible way consists in combining noble metals (Pt, Pd, Au ...) [5][6][7][8][9][10][11] and non-noble metals for preparing binary and ternary nanocatalysts. While non-noble metals are interesting from a cost reduction point of view, they may lead to reduced stability compared to pure platinum due to their dissolution capability [12][13][14][15][16][17]. Pt x Pd 1-x .…”
Section: Introductionmentioning
confidence: 99%
“…A possible way consists in combining noble metals (Pt, Pd, Au ...) [5][6][7][8][9][10][11] and non-noble metals for preparing binary and ternary nanocatalysts. While non-noble metals are interesting from a cost reduction point of view, they may lead to reduced stability compared to pure platinum due to their dissolution capability [12][13][14][15][16][17]. Pt x Pd 1-x .…”
Section: Introductionmentioning
confidence: 99%
“…14,[18][19][20][21][22] A comprehensive discussion of the ASAXS method and its use in characterizing carbon-supported metal catalysts can be found in several publications and textbooks. [23][24][25][26][27][28][29] One advantage this technique has is its ability to obtain element specific PSDs.…”
mentioning
confidence: 99%
“…From changes in the Pt and Cu PSDs obtained through ASAXS, Yu et al were able to show the in-situ formation of a Pt enriched shell surrounding a PtCu core through electrochemical Cu dissolution of a carbon supported Pt 25 Cu 75 electrocatalyst and Tuaev et al showed the same type of evolution for a Pt 25 Ni 75 electrocatalyst. 21,22 The ASAXS technique was used in this study to determine Pt PSDs of nanoparticle Pt 3 Co electrocatalysts in-situ and in-operando for two accelerated stress test protocols and ex-situ Pt and Co PSDs of the electrocatalyst before and after cycling. A catalyst with a Pt:Co atomic ratio of 3:1 was chosen for this study, as this ratio has been shown to have both the highest ORR activity and activity stability.…”
mentioning
confidence: 99%
“…F part (q, R) and F co (q, R c ) are the form factor for a spherical scattering object of radius R for the whole particle and of a radius R c for the core, respectively. Only a limited number of papers are dedicated to investigations of core-shell particles by SAXS technique [23][24][25], and even less by ASAXS technique [19,26,27]. Figure 3 shows data extracted from recent works of Haug and coworkers [27].…”
Section: Core-shell Bimetallic Particles In Matrixmentioning
confidence: 99%
“…contributing significantly to the total scattering signal. This is the case for metal catalyst particles in porous carbon support [9,[17][18][19][20]. As the carbon matrix is inhomogeneous, the system should be described using a three-phase model [21].…”
mentioning
confidence: 99%